Characteristics and prognostic values of abdominal aortic branches calcification in hemodialysis patients - Wen Shi; Xiaotong Xie; Yu Zhao; Yuqiu Liu; Xiaoliang Zhang (Renal Failure)
Background Vascular calcification is highly prevalent and associated with mortality in hemodialysis patients. However, extreme splanchnic arterial calcification in calciphylaxis with poor prognosis raises questions regarding the reliability of previous vascular calcification scoring methods. Therefore, this study aimed to examine the distribution characteristics of abdominal aortic branch calcification and identify a more reliable predictor of mortality in hemodialysis patients.Methods The cohort study included 237 hemodialysis patients. The distribution characteristics of abdominal aortic branch calcification were determined by quantifying the calcification volumes. The primary and secondary outcomes were all-cause mortality and new-onset cardiovascular events, respectively. We compared the prognostic values of abdominal aortic branch calcification and constructed a predictive nomogram model.Results The prevalence of abdominal vascular calcification in hemodialysis patients was 95.36%, with the highest prevalence in the abdominal aorta (88.61%) and internal iliac artery (85.65%). During a median follow-up period of 3.92 years, 137 patients died. Internal iliac artery and mesenteric artery calcification showed the greatest predictive values for mortality. Internal iliac artery calcification and serum albumin level were independently associated with mortality in hemodialysis patients (p < .001). The nomogram model constructed with internal iliac artery calcification, serum albumin level, age, and comorbid cardiovascular disease was well discriminative, calibrated, and clinically applicable for predicting 3-year survival.Conclusion Abdominal aortic branch calcification, particularly internal iliac artery calcification, is a preferable prognostic predictor than abdominal aorta or coronary artery calcification in hemodialysis patients.